A review of state-of-the-art reflective two-stage solar concentrators: Technology categorization and research trends. (October 2019) - Bushra, Nayab; Hartmann, Timo
Abstract: Every year a wide range of articles are published on reflective two-stage solar concentrators (TSSCs), that focus on either geometrical designs, performance characteristics, solar energy receivers, or applications. Among previous studies, no review article currently highlights all the aforementioned aspects to observe the overall research development of these systems. Therefore, this paper aims to develop a comprehensive analysis of reflective type TSSCs based on the review of research papers and patents and analyses the presented TSSC technologies along five categories: geometries, concentration ratio, optical performance, receivers, and applications. We found that the most dominant geometries applied in TSSC design were cassegrains and solar furnaces. Our review also shows that most papers focussed on applying TSSCs for power generation using solar cells, and thermo-electric generators. Most studied systems remained at medium, high and ultrahigh concentration level and medium to high optical efficiency. We also found that most studies only validated the proposed systems experimentally. Only a few studies focussing on solar furnaces have also been validated within large scale practical settings. The analytical results help to identify future research initiatives towards a wider spread practical implementation of TSSCs which emphasizes parametric modeling approach. Parametric models can provide a range of design alternatives which can be tested under multiple environmental conditions. Through joint use of receivers, these systems can be deployed for multiple applications. Additionally, development of cost-effective and energy efficient TSSCs further requires detailed feasibility studies, cost-benefit analysis, as well as, environmental impact analysis. Based on the categorization analysis and the proposed research initiatives, future research on TSSCs can proceed on a more solid footing. Highlights: We develop a comprehensive analysis of reflective type two-stage solar concentrators (TSSCs). We analyse TSSCs along five categories: geometries, concentration ratio, optical performance, receivers, and applications. Most studies only validated TSSCs experimentally. Only a few studies validated solar furnaces for large scale applications. Future research towards widespread practical implementation of TSSCs should aim parametric modeling and experimentation.